Direito, economia e organizações : uma análise dos deveres de proteção e diligência nos contratos de trabalho - Ribas, Juliana Rodrigues (2016)
This dissertation analyzes the contractual duties of employment relationship trough Law, Economics and Organization Theory, limiting the study to the employer’s duty to protect the employee and the employee from diligent work. This research, also, asks the conception of man in the Brazilian work contract seeks a more sophisticated answer considering the framework of the Consolidation of Labor Laws, explores the similarities and differences between the decision-making process of the employee and the employer, inquires the dogmas of conflict in Labor Law, that is presented since the 19th century, theme which inaugurates the First Chapter. Still, It presents the labor contract as the legal instrument that creates employment relations and legal subordination, investigating its subjects and refining legal rules about its existence, execution, termination and flexibility. This dissertation likewise ruminates on the duties in contractual labor relations, lists introductory notions of Economic Analysis of Labor Law, focusing on different economic perspectives of labor contracts, and defends the inclusion of ethical values into Economic Analysis of Law, focusing on the protection of employees in work accidents perception, environmental protection of work and human capital investment. Finally, this work ascertains the employee’s identification and commitment and its connection to diligence, the attempt to insert Brazilian Profit Participation in Labor Market and the connection between the job satisfaction and its turnover, thinking about the trust dynamics between the subjects in the employment relationships and about the influences of Brazil’s protectionist legal system; lastly, this work is concluded trough a proposal of reconciliation between work value and the pursuit of profit through the (re) adaptation of the decision-making process of the business organization.